Being lesbian : a barrier in employment in New Zealand secondary school? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Administration at Massey University - Bartlett, Carol (Massey University, 2003)
This thesis investigates the perceptions of secondary school teachers who are lesbian, specifically their perceptions of how sexual orientation affects their appointment to positions and also affects their promotion within New Zealand schools. A postal questionnaire was used to collect both quantitative and qualitative data from 67 self-selected participants. Their responses form the basis for the research findings. These responses are considered using various perspectives but mainly those of lesbian feminism. The research reveals that, even when it is illegal to discriminate in employment on the grounds of sexual orientation, many participants perceive that there are barriers to their appointment and promotion based on sexual orientation. This is particularly so in schools which serve small urban and rural areas. It is also so in schools of special (religious) character, which are exempt from the legislation. The study also highlights the many ways that teachers who are lesbian manage their sexual identities within their workplaces Based on these findings, recommendations for using this study, and for change, form the final section of this thesis.
Keywords: New Zealand Attitudes; Lesbian teachers; High school teachers; Sex discrimination in employment